The Politics of Representation of the G 30 S Incident at the Museum of Monumen Pahlawan Pancasila - Putri, Samantha Aditya (Journal of Philology and Historical Review, 2024)
The tragedy of the Movement on September 30th, 1965 by Indonesian Communist Party (G 30 S/PKI) has been widely considered as the most controversial history of Indonesia. The military generals, namely, Colonel Katamso, a Commander Military Resort Comman (Korem/Komando Rayon Militer) 072/Pamungkas, and Lieutenant Colonel Sugiyono, a Head Staff of Korem 072/Pamungkas, were assassinated during the tragedy. Because of the tragic event, the killing of these two military generals, the Soeharto government built a monument of commemoration for them in the Museum of Monumen Pahlawan Pancasila located in Padukuhan Kentungan, Daerah Istimewa Yogyakarta (DIY). This research expects to see how the Museum of Monumen Pahlawan Pancasila represents the tragedy of G 30 S/PKI. By using Stuart Hall’s theory of representation, the author interprets meanings and symbols through objects, displays, buildings, photos represented in the museum in order to deliver significant meaning to the public. This research explores primary and secondary data. The first one refers to historical work and anthropological fieldworks done in the research site in the museum, including observations, interviews, historic archive collections.  The research result shows that the museum represents the tragedy as a coup d’etat carried out by the communists to overthrow the legitimate government. PKI is negatively stigmatized as the mastermind of the tragedy G30S/PKI. Museum as political discourse constructed by the New Order government. Museum as an institution aims to disperse knowledge and produce meanings to lead the audience to a given meaning.